Flujo de agua subterránea y transporte en medios geológicos fracturados: una revisión - Marcos Adrián Ortega Guerrero (Revista Mexicana de Ciencias Geológicas)
The groundwater flow and the transport of solutes and contaminants in fractured media play a very important role in various hydrogeological and geological processes. Fractures are discontinuities that occur in practically all types of rocks, consolidated and semi-consolidated sediments, in which it has interacted with the hydrological cycle at different scales of space and time. This article reviews 20 years of research in the CGEO of different selected examples in Mexico, from local to regional scales, associated with 1) Gravitational Groundwater Flow Systems, 2) The hydrogeochemical interaction of groundwater with fractured rocks through which it circulates, 3) Instrumentation and coupled numerical analysis of flow parameters and time-varying geomechanics, during consolidation associated with pumping, 4) Analysis of fracture generation with the development and application of coupled flow and geomechanical equations, 5) Formation of new minerals, 6) Sustenance of ecosystems, 7) Artificial fracturing of soils for their conservation and infiltration of rainwater improvement; and on the issue of transport in 8) Natural solute migration mechanisms, 9) Contaminants induced by pumping, 10) Spills of hydrocarbon derivatives in low permeability and double porosity media due to fracturing and 11) Heat. The results show the importance of fractured media in groundwater recharge in mountainous areas and flow towards granular media in quantity and quality, where residence times of a few years to thousands are involved, which implies modifying water and ecosystem management criteria, in the country; the complexity of these processes requires different methodologies for their evaluation, among them the instrumentation and calibration of numerical models from 1D to 3D for analysis, predictions and the proposal of restoration, sustainability and management solutions; they also help to prevent, control and mitigate the negative impacts on health and the environment caused by the induction of geogenic elements and by various types of pollutants; fractured media also support numerous terrestrial and marine ecosystems, and in the case of damaged agricultural soils, artificial fracturing allows increasing rainwater infiltration and improving productivity in adaptation to climate change and reducing the extraction in aquifers where safe capacity has been exceeded; unfortunately, excessive extraction in closed basins is causing fracturing of the aquitards, both hydraulic and due to differential settlement, which favors the migration of pore water rich in elements harmful to human health and the environment, whose natural function was its protection. All this requires designing mechanisms for the transfer of scientific knowledge to society and decision makers to propose novel restoration and sustainability strategies, under the new paradigm of Gravitational Groundwater Flow Systems.